Accuracy and Judgment Bias of Low Intensity Emotional Expression Among Individuals with Major Depression - Bakerman, Davina (Université d'Ottawa / University of Ottawa, 2013)
It has been suggested that depressed individuals have difficulties decoding emotional facial expressions in others contributing to a negative cycle of interpersonal difficulties. Some studies have demonstrated global deficits in the processing of emotional facial expressions compared to non-depressed participants, whereas others have noted differences for specific emotions. Methodological issues, including the operationalization of accuracy and bias and the examination of a limited range of emotion and intensity, can partially explain the mixed findings. The aim of the current study was to examine differences in accuracy in the detection of emotional facial expressions in participants with MDD (currently depressed, partially remitted, and those with a lifetime history of MDD) and non-depressed comparisons. Methodological limitations of previous studies were addressed by: (a) using the unbiased hit rate (Wagner, 1993), which is a more precise measure of accuracy for specific emotion, (b) using a more precise measure of judgment bias, taking into account the overuse or underuse of specific emotion categories, (c) including the six basic emotions, and (d) incorporating expressions ranging from 20%-100% intensity. Of secondary interest was to determine whether transient mood state is predictive of accuracy scores regardless of diagnostic status. Thirty-seven depressed and 34 non-depressed participants recruited from the ROHCG Mood Disorders program and the University of Ottawa took part in this study. Clinical status was assessed using the Structured Clinical Interview for the DSM-IV (SCID-IV) and the Beck Depression Inventory-II (BDI-II). Participants also completed the Profile of Mood States-Bipolar (POMS-BI) form to assess mood state at the time of testing. The facial recognition task consisted of happiness, sadness, anger, fear, disgust, and surprise at 20%-100% intensity, presented for 500 ms. Participants pressed a computer key to identify the emotion that was presented. Results indicated that both groups of depressed participants were more accurate than non-depressed participants in detecting anger at 20% intensity. Depressed participants also showed a bias away from surprise. Group differences at high intensity were non-significant, however, participants with current depression and partial remission showed a bias towards anger at 50% intensity. Regression analyses were performed using the POMS-Agreeable Hostile (POMS-AH) and POMS-Elated Depressed (POMS-ED) scales to determine whether mood state was predictive of accuracy in the detection of anger and sadness. Regression models predicting accuracy were non-significant. Results of this study are considered in the context of cognitive and cognitive-interpersonal theories of MDD.
Keywords: Facial expressions; Depression; Accuracy; Bias